Implementation of Discipline Character Education Through Scout Activities at SDN Grujugan Lor 1 Bondowoso - Fajar, Delan Wardhana; Cholifah, Puri Selfi; Ahdhianto, Erif (Universitas Pendidikan Indonesia (UPI), 2024)
Disciplined character education through scout activities is an effort to develop and familiarize scout members to become disciplined individuals. This research aims to describe the implementation of disciplined character education through scout activities at SDN Grujugan Lor 1. This type of research is descriptive qualitative. The informants in this research were school principals, scout leaders and scout members. Data collection in research uses observation, interviews and documentation. Data were analyzed through data reduction, data presentation and conclusions. Data validity checking techniques use extended observations, increased persistence, and triangulation. The results of this research show that scout leaders implement disciplined character through scout activities including 4 discipline indicators, namely time discipline, discipline in obeying rules, attitude discipline, and worship discipline. Scout leaders in implementing disciplined character education through scouts apply strategies by providing advice, example, habituation, and punishment or sanctions for those who break the rules. Supporting factors are that the scoutmaster has completed the basic (KMD) and advanced (KML) scoutmaster courses, full parental support, and complete infrastructure. The inhibiting factors are the large number of scout members, short time, and there are some scout members or students who don't like scout activities